Effect of polymer species and concentration on the production of mefenamic acid nanoparticles by media milling - Peukert, Wolfgang; Ito, A; Konnerth, Christoph-Günther; Schmidt, Jochen (European Journal of Pharmaceutics and Biopharmaceutics, 2016)
The effect of four structurally different polymer species (hydroxypropylcellulose, polyvinylpyrrolidone, vinylpyrrolidone-vinyl acetate copolymer and polyvinyl alcohol) on the production of mefenamic acid nanoparticles during media milling has been studied. It was found that product particle sizes are strongly determined by the type of polymeric stabiliser as well as by its concentration at constant process conditions. With respect to small product particle sizes an optimum excipient concentration was identified and adjusted for colloidal stability of the drug nanosuspensions. Furthermore, it was found that overdosing of excipients must be omitted to suppress ripening due to enhanced solubilisation phenomena. Hence, the smallest product particle sizes were obtained using a polymeric stabiliser which exhibits a high affinity to the model drug compound and a low solubilisation capacity. Affinities of each polymer species to mefenamic acid and corresponding surface concentrations were determined using straightforward and simple viscosity measurements of the supernatant. A relationship between polymer affinity, solubilisation capacity and limiting product particle size has been observed, which supports the hypothesis that final product particle sizes are rather determined by the solid-liquid equilibrium than by pure mechanical fracture.
Keywords: Active pharmaceutical ingredient; Formulation; Media milling; Mefenamic acid; Nanosuspension; Ripening; Solubilisation; Solubility; Surface concentration